Jihad and terrorism: an alternative explanation - Moniruzzaman, Md. (The Kripke Center, 2008)
Jihad (Islamic holy war) is a fundamental foreign policy concept in Islam. Following the 9/11 incident, a considerable number of scholarly works in the West have squarely equated jihad with terrorism. In recent Islamic scholarship as well, the usage of the concept either tends to be avoided or is increasingly being depoliticized. The popular understanding of the concept has made it a necessary evil. This article argues that jihad is not just a war, rather it can be understood from a universal humane perspective and its philosophical moral principles can be used in greater human and social welfare.